Thermodynamic prediction of biogas production and combustion: The spontaneity and energy conversion efficiency from photosynthesis to combustion - Endalkachew Addis Mekonen; Yonas Tibebu Mekonnen; Samuel O. Fatoba (Scientific African, 2023)
Due to inappropriate energy consumption and subpar waste management, the growing population leads to an increase in energy demand and environmental damage. The creation of biogas enhances the management of organic waste and provides renewable energy. The production of biogas, which is a mixture of several gases, primarily methane and carbon dioxide, occurs during the four phases of aerobic digestion (AD). The four stages are hydrolysis, acidogenesis, acetogenesis, and methanogensis. Biogas comprises 50–70% Methane, 25–40% carbon dioxide and remaining traces of gases. In this paper, these biogas production processes are not thoroughly studied utilizing thermodynamic principles. Using thermodynamic criteria, this article analyses and assesses why the aerobic digesting process is spontaneous. Entropy, enthalpy, and Gibbs free energy of reactions during the various stages of the formation of biogas are examined. At Standard Temperature and Pressure Conditions (STP), the combined four phases of biogas formation are exothermic and spontaneous based on the analysis of Entropy, enthalpy, and Gibbs free energy of reactions from balanced equations at standard conditions of temperature and pressure. A unit mole of glucose is used to compare the energy released during photosynthesis with the energy released during biogas burning. Three moles of methane can be produced from decomposition of glucose. The combustion of three moles of methane yields 2406.876 kJ energy and if the same amount of moles of biogas (60% methane and 40% carbon dioxide) burns the energy yield is reduced to 1604.584 kJ. From the energy captured by photosynthesis i.e., 2808.1 kJ/mol 57.141% of the energy is recovered in the biogas combustion process. This efficiency reaches to 85.711% if pure methane is burned. As the separation of methane from biogas, mixture in actual plants is not economically feasible the combustion of methane gas the ideal limit of the efficiency.